2022
DOI: 10.3390/ijerph19042456
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Diarrheal Episodes in an Agricultural Community in Nam Dinh Province, Vietnam: A Prospective Cohort Study

Abstract: In Vietnam, data on the risk factors for diarrhea at the community level remain sparse. This study aimed to provide an overview of diarrheal diseases in an agricultural community in Vietnam, targeting all age groups. Specifically, we investigated the incidence of diarrheal disease at the community level and described the potential risk factors associated with diarrheal diseases. In this prospective cohort study, a total of 1508 residents were enrolled during the 54-week study period in northern Vietnam. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The overall incidence of disease in children under-five was found to be higher when compared with a Vietnamese cohort study which showed 0.81 episodes. 22 However, a review article in India demonstrated a similar trend. 23 Our study targeted only children under the age of five years whereas, the Vietnamese study targeted all age groups.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The overall incidence of disease in children under-five was found to be higher when compared with a Vietnamese cohort study which showed 0.81 episodes. 22 However, a review article in India demonstrated a similar trend. 23 Our study targeted only children under the age of five years whereas, the Vietnamese study targeted all age groups.…”
Section: Discussionmentioning
confidence: 86%
“…The incidence rate in this cohort also showed wide variation with research from geographically, and culturally similar regions. 22,23 The unexpectedly low diarrhea prevalence among children from our baseline study 17 suggests a decreased transmission of diarrhea, perhaps because many families participating in the study had access to improved water sources, sanitation, and behavioral change due to FCHV's active role in those areas. At the time of the study, rotavirus vaccine had not been introduced into the national immunization program in Nepal.…”
Section: Discussionmentioning
confidence: 94%
“…The infrastructure, medical systems, and food production and food marketing systems that contribute to the improving public health are being developed. However, childhood diarrhea remains a public health problem in Vietnam [2].…”
Section: Introductionmentioning
confidence: 99%
“…In a scientific report published in 2012, it was stated that nearly 7 million children under the age of 5 died due to preventable and treatable diseases, and diarrhea was responsible for approximately 10% of these deaths [6]. It has been reported that children under 5 years of age have an average of 3 episodes per year in developing countries, while one (or less) episode of gastroenteritis in developed countries [7][8][9].…”
Section: Introductionmentioning
confidence: 99%